2008
DOI: 10.1095/biolreprod.107.066316
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Acrosome Reaction in Black Tiger Shrimp (Penaeus monodon) Requires Sperm Trypsin-Like Enzyme Activity1

Abstract: Trypsin-like enzymes in egg water (EW), a natural acrosome reaction (AR) inducer, are known for their importance in shrimp AR. In this report, we describe a unique phenomenon of the AR of black tiger shrimp (Penaeus monodon) sperm. It was completed within 45-60 sec and comprised only the acrosomal exocytosis and depolymerization of the sperm head anterior spike. We used peptidyl fluorogenic substrates to show the presence of trypsin-like enzymes in P. monodon EW and sperm, but minimal activities of chymotrypsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…In our study, the spermatozoa exhibit the shape of a small umbrella due to the development of a long spike. The function of this spike seems to be involved in the fertilization of ovocites (Lynn and Clark 1983;Demestre et al 1997;Kruevaisayawan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the spermatozoa exhibit the shape of a small umbrella due to the development of a long spike. The function of this spike seems to be involved in the fertilization of ovocites (Lynn and Clark 1983;Demestre et al 1997;Kruevaisayawan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, the most well‐recognized glycoconjugate studies in invertebrates are the reports on echinoderms in which the glycopolymer in their egg jelly was identified as a fucose‐sulfate polymer (Alves, Mulloy, Moy, Vacquier, & Mourao, ; Mulloy, Ribeiro, Alves, Vieira, & Mourao, ; Vilela‐Silva et al, ) that was shown to possess primary physiological functions in species‐specific gamete interactions and in modulating the AR response (Alves, Mulloy, Diniz, & Mourao, ; Vacquier & Moy, ; Vilela‐Silva, Castro, Valente, Biermann, & Mourao, ). The existence and function of sulfated glycoproteins has been shown in many other invertebrate and vertebrates species (Pomin, ; Sylvester, Morales, Oko, & Griswold, ), but not in some marine shrimp and abalone (Kruevaisayawan et al, ; Kruevaisayawan et al, ). This discrepancy could simply reflect the nature of species’ differences in their glycosylation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Murine SERPINE2 is an important factor synthesized in the seminal vesicle and secreted into seminal fluid, which functions as a sperm decapacitation factor that binds with sperm and inhibits proteolytic activity until final maturation and capacitation in the oviduct (Lu et al, ). In P. monodon , successful induction of the sperm acrosome reaction required trypsin‐like protease activity (Kruevaisayawan et al, ). Sperm treated with protease inhibitors showed a decreased ability to undergo the acrosome reaction, while the acquisition of sperm trypsin‐like protease activity indicated the complete maturation of sperm for fertilization.…”
Section: Discussionmentioning
confidence: 99%